2019
DOI: 10.2478/rrlm-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of selected snake venoms on pathogenic bacterial strains

Abstract: Snake venoms are aqueous solutions containing peptides and proteins with various biochemical, physiological, and pathophysiological effects. Several snake venom components are used as lead molecules in the development of new active substances for the treatment of cardiovascular diseases, clotting disorders, cancer or pain. Antibacterial activity has also been attributed to snake venoms and proteins isolated from snake venoms. This study provides information regarding the antibacterial activity of venoms obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Aside from their predictive value, it is crucial to consider the underlying antibacterial mechanisms of protein components individually as well as their functional interactions. Although specific proteins within a protein family may differ between venoms, they exhibit similar cytotoxic activities [28,[36][37][38]. For all Elapidae, our analyses suggest PLA 2 , svMP, and WAP/KUN as the best predictors for antibacterial effectiveness.…”
Section: Predictions Vs Mechanismsmentioning
confidence: 76%
“…Aside from their predictive value, it is crucial to consider the underlying antibacterial mechanisms of protein components individually as well as their functional interactions. Although specific proteins within a protein family may differ between venoms, they exhibit similar cytotoxic activities [28,[36][37][38]. For all Elapidae, our analyses suggest PLA 2 , svMP, and WAP/KUN as the best predictors for antibacterial effectiveness.…”
Section: Predictions Vs Mechanismsmentioning
confidence: 76%
“…In the present study, antibacterial activity was not found for S. aureus and E. coli but was determined for Pseudomonas aeruginosa, obtaining a MIC of 50 and a MBC of 100 µg/mL for C. triseriatus and C. ravus (CT2 and CR3). According to Boda et al, 2019, the antibacterial activity of venoms from viperid species is probably due to their content of proteins with proteolytic activity [19].…”
Section: Antibacterial Activitymentioning
confidence: 99%